Naughts and Crosses - Blackman, Malorie (London : Corgi, 2012)
In a world where the pale-skinned Naughts are discriminated against by the politically and socially powerful dark-skinned Crosses, teenagers Callum--a Naught--and Sephy--a Cross--test whether their love is strong enough to survive their society's racism.
Keywords: Conduct of life -- Fiction; Interpersonal relations -- Fiction; Love -- Fiction; Prejudices -- Fiction; Race relations -- Fiction; Racism -- Fiction